Contemporary macrocycles for discrete polymetallic complexes: precise control over structure and function. (11th August 2021) - Chaudhry, Mohammad T.; Akine, Shigehisa; MacLachlan, Mark J.
Abstract : Macrocycles have unique cavities that can function as templates for multimetallic complexes. Abstract : The growth of multimetallic clusters and complexes can proceed in the presence of suitable ligands, but often leads to polydisperse structures with poor solubility. As an alternative approach, macrocyclic molecules can anchor the multimetallic complex, directing its formation and stabilizing the resulting product. This approach can provide excellent control over the growth of clusters, and offers a handle to control solubility and other properties of the resulting complexes. In this Tutorial Review, we discuss recent activity (primarily the last two decades) directed at the controlled and reproducible synthesis of multimetallic complexes using macrocyclic ligands. Throughout the review, we focus on the unusual structures that are only accessible by using macrocycles as ligands, and their unique properties.